2023
DOI: 10.3390/jcm12134248
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of the Intensification of Canagliflozin Dose from 100 mg to 300 mg Daily in Patients with Type 2 Diabetes in Real Life: The INTENSIFY Study

Abstract: Aim: This study aimed to evaluate the effectiveness and tolerability of intensifying the dose of canagliflozin from 100 mg/day (CANA100) to 300 mg/day (CANA300) in patients with type 2 diabetes (T2DM) and suboptimal metabolic control in a real-world setting. Methods: A multicenter observational study was conducted on adult patients with T2DM who initiated treatment with CANA100 and subsequently required intensification to CANA300. The primary outcome measures were changes in HbA1c and weight at 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The CVD-REAL 3 study provided further real-world evidence concerning the impact of SGLT2is in decelerating kidney function decline ( p < 0.0001) and the risk of major kidney events ( p < 0.0001), compared with other oral glucose-lowering therapies [ 51 ]. Moreover, recent real-world data showed that increasing canagliflozin dosage to the highest approved level in individuals with T2DM and less-than-optimal metabolic results led to notable enhancements in key factors including fasting plasma glucose, HbA1c, body weight and blood pressure, complementing the existing cardiorenal protection offered by lower-dose therapy [ 52 ]. Real-world studies reaffirmed well-established data from large randomised controlled cardiovascular outcomes trials (CVOTs; EMPA-REG Outcome, CANVAS, DECLARE-TIMI 58), which have provided an ever-expanding body of evidence regarding SGLT2i-related reductions in CV events, including composite endpoints that encompass major adverse cardiovascular events (MACE), heart failure (HF) and CV death, HHF and worsening HF events [ 17 , 18 , 53 ].…”
Section: Back To Basics In T2dm Management: Improving Quantity and Qu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The CVD-REAL 3 study provided further real-world evidence concerning the impact of SGLT2is in decelerating kidney function decline ( p < 0.0001) and the risk of major kidney events ( p < 0.0001), compared with other oral glucose-lowering therapies [ 51 ]. Moreover, recent real-world data showed that increasing canagliflozin dosage to the highest approved level in individuals with T2DM and less-than-optimal metabolic results led to notable enhancements in key factors including fasting plasma glucose, HbA1c, body weight and blood pressure, complementing the existing cardiorenal protection offered by lower-dose therapy [ 52 ]. Real-world studies reaffirmed well-established data from large randomised controlled cardiovascular outcomes trials (CVOTs; EMPA-REG Outcome, CANVAS, DECLARE-TIMI 58), which have provided an ever-expanding body of evidence regarding SGLT2i-related reductions in CV events, including composite endpoints that encompass major adverse cardiovascular events (MACE), heart failure (HF) and CV death, HHF and worsening HF events [ 17 , 18 , 53 ].…”
Section: Back To Basics In T2dm Management: Improving Quantity and Qu...mentioning
confidence: 99%
“…The EMPA-KIDNEY (empagliflozin) and DAPA-CKD (dapagliflozin) trials showed similar results in individuals with CKD, whether or not they had T2DM [ 21 , 28 , 31 ]. SGLT2i use has also been typically associated with the lowering of other CV risk factors, such as blood pressure, and recipients often experience weight loss [ 2 , 12 , 17 , 18 , 34 , 35 , 49 , 52 , 53 , 57 60 ]. Organ protection remains the cornerstone objective for long-term management of T2DM and the wider implementation of SGLT2is early in the therapeutic pathway would support better outcomes through the lowering of both macrovascular risk and complication severity [ 1 4 , 12 , 17 23 , 28 , 31 , 35 , 52 , 53 , 56 , 61 ].…”
Section: Back To Basics In T2dm Management: Improving Quantity and Qu...mentioning
confidence: 99%